Modulation of Reaction Times and Sense of Agency via Subliminal Priming in Functional Movement Disorders - Huys, Anne-Catherine M. L.; Edwards, Mark J.; Bhatia, Kailash P.; Haggard, Patrick (Frontiers in Neurology, 2020)
Background: In functional movement disorders, explicit movements are impaired, while implicit movements are preserved. Furthermore, there is evidence that the sense of agency is abnormal. Aim: We aimed to investigate how motor responses and sense of agency were affected by subliminal or supraliminal cues in people with functional movement disorders. Methods: Twenty-three people with a functional movement disorder and 26 healthy controls took part in a subliminal and supraliminal priming experiment which investigated reaction times, choice and sense of agency. Participants pressed a left or right arrow key in response to an imperative left or right pointing arrow. Either key could be pressed in response to bidirectional arrows. The imperative arrow was preceded by a small left or right pointing prime arrow, that was non-predictive (50% correct) and was presented in either subliminal or supraliminal conditions. The participant’s response caused the appearance of a coloured circle and they rated the degree of control they felt over its appearance (sense of agency). The circle’s colour depended on whether their response was congruent or incongruent with the prime arrow direction. After exclusion, 19 participants remained in each group. Results: Prime-compatible responses led to faster reaction times in both the subliminal and supraliminal condition. Subliminal prime-compatible responses were chosen more frequently in the free choice condition. The sense of agency did not depend on prime-response congruency. There were no significant differences in any of these measures between the two groups. Conclusion: With non-predictive cues, reaction times, choices and the sense of agency remain normal in people with functional movement disorders, for both subliminal and supraliminal primes. The findings suggest that it is not so much conscious awareness of the movement, but rather conscious motor preparation that is detrimental to motor function in functional movement disorders.